Empowerment, Job Involvement, and Socio-demographic Characteristics: The Case of Part-Time Faculty Members - Shrestha, Prakash; Bhandari, Sita (Journal of Innovation in Academia, 2024)
This paper aims to assess the extent of perceived empowerment and job involvement among part-time faculty members. It also examines the relationship between empowerment and job involvement among part-time faculty members and explores how socio-demographic characteristics influence the relationship between empowerment and job involvement among part-time faculty members. It uses a descriptive and correlational research design to describe the levels of job involvement and empowerment among part-time faculty members and explore the relationships between these variables and socio-demographic characteristics. A scientifically prepared questionnaire is used to collect the primary data by considering various demographic characteristics, job involvement, and empowerment of part-time faculty on 10 constituent campuses. These campuses are selected judgmentally and conveniently. In total, 200 questionnaires are distributed to the part-time faculty members of different fields, and 133 usable questionnaires are returned, thereby yielding a response rate of about 66.50 percent. The results show a very strong positive association between job involvement and empowerment. This suggests that as part-time faculty members feel more empowered, their level of job involvement also increases significantly. High empowerment, which includes having a sense of meaning and competence, self-determination, and impact, is strongly associated with high job involvement. Only marital status and education are the two most important socio- demographic characteristics that have an impact on the association between job involvement and empowerment.